Mechanisms of antidiarrhoeal effects by diosmectite in human intestinal cells - Vittoria Buccigrossi; Carla Russo; Amedeo Guarino; Maiara Brusco de Freitas; Alfredo Guarino (Gut Pathogens, 2017)
Abstract Background Rotavirus (RV) induces diarrhoea through a sequence of enterotoxic and cytotoxic effects. The former are NSP4-dependent, induce calcium-dependent chloride secretion and involve oxidative stress. Diosmectite (DS) is a natural clay that has been recommended as an active therapy for diarrhoea, but the mechanism of its effect is not clear. Electrical parameters may be used to measure the direct enterotoxic and cytotoxic effects in polar epithelial intestinal cells. To investigate the effects of DS on RV-induced enterotoxic and cytotoxic damage. Caco-2 cells were used as a model of RV infection to evaluate chloride secretion, epithelial integrity, oxidative stress and viral infectivity in Ussing chambers. Results Diosmectite reduced the expression of NSP4 and oxidative stress, resulting in a strong inhibition of chloride secretion. Preincubating RV with DS reduced the cytotoxic effect. Finally, the viral load was reduced by DS but not by control clay. This result suggests that DS specifically affects the early events of RV infection protecting the enterocyte, whereas it does not restore already-established cell damage. Conclusion These findings indicate that DS exerts an anti-diarrhoeal effect by inhibiting viral replication and the expression of NSP4. Both ion secretion and cell damage induced by RV are strongly inhibited consequent to the antiviral effect, which explains its clinical efficacy.